Developing of guidance for laboratory practice of islamic science-integrated plant anatomy-physiology - Ahmad Ali; Wiwin Pramita Arif (Universitas Negeri Jakarta, 2019)
The research aims to develop a valid, effective, and practice guidance for laboratory practice of Islamic science-integrated plant anatomy-physiology. The study is development research of Plomp development model. The study consists of five phases, namely the preliminary investigation phase, design phase, realization or construction phase, test, evaluation, and revision phase, and implementation phase. Devices developed were tested to students of Biology Education Department, Universitas Islam Negeri (UIN) Alauddin, Makassar in the Even Semester 2017/2018 Academic Year. The research results indicate that the laboratory practice guidance developed has met valid criteria with content validation average of one practice criteria with device applicability in category three meaning that most of the devices are implemented. Effective criteria with 92% of students who performed the laboratory practice give positive responses to the overall item questioned, and 100% assistants provide positive response on 93.33% items asked.